Fluoride Varnish with Antibacterial Agents for Dental Caries Prevention: A Short Review on Its Fabrication - Reagan Cendikiawan; Yosi Kusuma Eriwati (Journal of Indonesian Dental Association, 2023)
Introduction: In recent years, the medical field has begun to use medicinal plant in the manufacture of modern medicines. Most of the medicinal plants used have antibacterial properties such as cinnamon, clove, betel, and holy basil. These medicinal plants could be used in the manufacture of fluoride varnish to support antibacterial properties in preventing the development of dental caries. Objective: This study aimed to provide update review of medicinal plant used as antibacterial agent in the fabrication of fluoride varnish to prevent dental caries. Method: Data collection were carried out by searching the literature on article search sites, namely PubMed and Scopus which were published from 2017 to 2022. Data searches were carried out systematically using the keywords fluoride varnish, dental caries, antibacterial, and fabrication. The author performs data search, data selection, and data extraction. Results: Only nine articles were found after a thorough selection process and database search using search terms and keywords. Seven of the studies were in vitro study and two was randomized clinical trial (RCT). In the overall fluoride varnish efficacy study, adding medicinal plant as an antibacterial agent showed strong antibacterial action against S. mutans with great bacterial inhibition zone. Together with its constituent parts, the fabricating method, such as the temperature and stirring rate, influence the optimal result of fluoride varnish. Conclusion: The addition of medicinal plants and method modification in the fabrication of fluoride varnish showed potential antibacterial properties that enhance higher fluoride release.